2022
DOI: 10.1186/s12935-022-02612-z
|View full text |Cite
|
Sign up to set email alerts
|

A review on the role of DANCR in the carcinogenesis

Abstract: DANCR is an RNA gene located on chr4. This gene has several splice variants. Up-regulation of DANCR has been reported in many types of cancers. This lncRNA is mainly located in the cytoplasm and regulates genes expression at post-transcriptional level. In fact, it acts as a molecular sponge for a variety of miRNAs, including miR-874-3P, miR-335, miR-149, miR-4319, miR-758-3p, miR-216a-5p, miR-874-3p, miR-33a-5p, miR-335-5p, miR-145-3p, miR-665, miR-345-5p and miR-125b-5p. DANCR also regulates activity of PI3K/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
0
7
0
1
Order By: Relevance
“…S1F ). The coding potential calculator 2 (CPC2) [ 16 ] and coding potential assessment tool (CPAT) [ 17 ], with two famous lncRNAs HOTAIR [ 18 , 19 ] and DANCR [ 20 ] as positive control, predicted weak protein-coding potential for LINC00880 (Fig. 1F ), which was further confirmed by phyloCSF [ 21 ] (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…S1F ). The coding potential calculator 2 (CPC2) [ 16 ] and coding potential assessment tool (CPAT) [ 17 ], with two famous lncRNAs HOTAIR [ 18 , 19 ] and DANCR [ 20 ] as positive control, predicted weak protein-coding potential for LINC00880 (Fig. 1F ), which was further confirmed by phyloCSF [ 21 ] (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Laboratory studies have found that overexpression of DANCR can promote the proliferation, invasion, and metastasis of liver cancer cells and inhibit apoptosis [46] . In addition, DANCR can regulate various signaling pathways, such as Wnt/β-catenin, PI3K/AKT, etc [47] , participating in the occurrence and development of liver cancer. These ndings provide strong evidence for our inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have found that overexpression of DANCR can promote the proliferation, invasion, and metastasis of liver cancer cells and inhibit apoptosis 45 . In addition, DANCR can regulate various signaling pathways, such as Wnt/β-catenin, PI3K/AKT, etc 46 , participating in the occurrence and development of liver cancer. These findings provide strong evidence for our inferences.…”
Section: Discussionmentioning
confidence: 99%